ANALYSIS OF THE QUALITY OF MANAGEMENT OF STUDENT SERVICES DURING THE COVID-19 PANDEMIC IN REMBANG 2 - Ambar Chess Subekti; Andri Trianfano; Sartono Sartono (Department of Public Administration, University Wijaykusuma Purwokerto, 2022)
This research is entitled “Analysis of the Quality of Student Service Management During the Covid 19 Pandemic Period at the State Junior High School (SMP) 2 Rembang, Purbalingga Regency. The purpose of this study was to describe and explain the quality of student service management during the covid 19 pandemic at the State Junior High School (SMP) 2 Rembang, Purbalingga Regency. This research method is descriptive qualitative. Informants were determined by purposive sampling method. The analysis of research results using an interactive analysis model. Based on the results of the study, several conclusions can be drawn as follows: (1). The service procedure has been clearly and comprehensively formulated, the completion time has been determined; (2). Service completion time is only 2 hours according to the specified time. Obstacles in completing work can not be separated from the internet network; (3). The service fee set by SMP Negeri 2 Rembang, Purbalingga Regency is free; (4). Service Products, the quality of student service management during the Covid 19 Pandemic in accordance with the provisions that have been set. The results of the service that will be received correctly and appropriately according to the needs of the applicant; (5). Facilities Service infrastructure in general is very adequate, completeness of tools (computer, internet, etc.) is adequate; (6). The competence of service providers, administration is very mastery according to the main tasks and functions of each. Based on the conclusions of the research results above, the proposed implications are: (1). Improving the skills of administrative staff so that they are more reliable in their respective duties and functions; (2). During the Covid 19 pandemic, many programs were delayed, so especially in the even semester of the 2020/2021 academic year many activities were not carried out, therefore student management planning needed to be carried out by holding a meeting to draw up a plan in student management that was made at the beginning academic year with the school, principal and structural.